2017
DOI: 10.1093/mnras/stx1461
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of methyl isocyanate ices under astrophysical conditions

Abstract: Methyl isocyanate has been recently detected in comet 67P/ Churyumov-Gerasimenko (67P/CG) and in the interstellar medium. New physicochemical studies on this species are now necessary as tools for subsequent studies in astrophysics. In this work, infrared spectra of solid CHNCO have been obtained at temperatures of relevance for astronomical environments. The spectra are dominated by a strong, characteristic multiplet feature at 2350-2250 cm, which can be attributed to the antisymmetric stretching of the NCO g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In the unprocessed samples the ν a -NCO band, with its characteristic quadruplet structure, stands out at 2400-2200 cm -1 . There are some differences in the peak positions and in the band profiles between the spectra of pure methyl isocyanate and those of methyl isoyanate diluted in water ice, but the characteristic quadruplet structure is present in both cases (see Maté et al 2017 for a discussion on the IR spectroscopy). The ν a -NCO band is the most intense IR absorption of methyl isocyanate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the unprocessed samples the ν a -NCO band, with its characteristic quadruplet structure, stands out at 2400-2200 cm -1 . There are some differences in the peak positions and in the band profiles between the spectra of pure methyl isocyanate and those of methyl isoyanate diluted in water ice, but the characteristic quadruplet structure is present in both cases (see Maté et al 2017 for a discussion on the IR spectroscopy). The ν a -NCO band is the most intense IR absorption of methyl isocyanate.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra were recorded with a resolution of 2 cm -1 using a HgCdTe (MCT) detector refrigerated with liquid nitrogen. The gas phase composition during deposition was monitored by means of a calibrated quadrupole mass spectrometer (QMS) placed in an adjacent chamber (Maté et al 2017). The base pressure in the vacuum chamber was ~ 0.7-1×10 -8 mbar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl isocyanate was prepared with a modified version of the synthesis of Han et al 26 as reported in Maté et al 27 A few grams of the sample were placed in a vial attached to the experiment. The vial was plunged into a chiller set at −40 • C to lower the vapor pressure to around 10 −1 mbar, which was otherwise 280 mbar at 0 • C. This step was necessary to avoid too great a build-up of the sample in the experiment which could lead to polymerization or blockages, but also to limit the consumption of the sample.…”
Section: A Ch 3 Nco Tpes and Photoion Yield Recordingmentioning
confidence: 99%
“…The parent species of CH 3 NCO has been prepared as previously reported (Maté et al 2017). The syntheses of Han et al (1989) have been modified to prepare CH 3 N 13 CO and 13 CH 3 NCO.…”
Section: Chemical Synthesismentioning
confidence: 99%